Penerapan Metode Pembelajaran Think Pair Share pada Pelajaran Pendidikan Agama Islam Kelas VII Berbasis Kurikulum Merdeka di Sekolah Menengah Pertama Islam Raudlatul Ulum Brankal Kabupaten Jombang - Rohmah, Nailul; Waslah, Waslah; Huda, Saihul Atho Alaul (Lembaga Yasin AlSys, 2025)
The Think Pair Share method is one of the important learning methods that should be implemented in teaching and learning activities, as it is designed to encourage students to seek answers to problems or questions through group discussions. The problem formulation in this study is the activity level and the supporting and inhibiting factors in the implementation of the Think Pair Share learning method. This type of research is qualitative research that focuses on collecting descriptive data through direct interaction. Data analysis is conducted through three stages: direct observation, interviews, and documentation. The supporting factors in the Think Pair Share method include the ease of planning and implementing learning, as well as facilitating students' understanding of the subject matter, in addition to adequate facilities and infrastructure. Meanwhile, the inhibiting factors in the learning process are certain limitations. The solutions and efforts made based on the supporting and inhibiting factors identified by the researcher include monitoring students who experience difficulties and lack concentration, recognizing students' characteristics, creating a comfortable and clean learning environment, and enhancing students' literacy at home through book reading assignments.